Genetically-modified human mesenchymal stem cells to express erythropoietin enhances differentiation into retinal photoreceptors: an in-vitro study - Lee, Suet Shirley Ding; Ee-Hwan, Avin Koh; Kumar, Suresh; Ali Khan, Mohammed Safwan; Alzahrani, Badr; Mok, Pooi Ling (Elsevier BV, 2019)
Dysfunctional or death of retinal photoreceptors is an irreversible phenomenon that is closely associated with a broad range of retinal degenerative diseases, such as retinitis pigmentosa and age-related macular degeneration (AMD), resulting in successive loss of visual function and blindness. In search for viable treatment for retinal degenerative diseases, mesenchymal stem cells (MSCs) has demonstrated promising therapeutic capabilities to repair and replace damaged photoreceptor cells in both in vitro and in vivo conditions. Nevertheless, the dearth of MSC differentiation capacity into photoreceptors has limited its use in cell replacement therapy. Erythropoietin (EPO) has vital role in early neural retinal cell differentiation and demonstrated rescue potential on dying photoreceptor cells. Hence, we aimed to evaluate the differentiation capacity of MSCs into photoreceptor cells in the presence of human EPO protein. We derived the MSC from human Wharton's jelly of umbilical cord and transduced the cells with lentivirus particles encoding EPO and green fluorescent protein (GFP) as reporter gene. The transduced cells were selectively cultured and induced to differentiate into photoreceptors by exposing to photoreceptor differentiation cocktail. Our preliminary results showed that transduced cells exposed to induction medium had an enhanced differentiation capacity when compared to non-transduced cells. Our results demonstrated a novel strategy to increase the yield of in vitro photoreceptor differentiation and may be potentially useful in improving the efficiency of stem cell transplantation for ocular disorders.